2017
DOI: 10.1038/emm.2016.167
|View full text |Cite
|
Sign up to set email alerts
|

TMF and glycitin act synergistically on keratinocytes and fibroblasts to promote wound healing and anti-scarring activity

Abstract: Keratinocyte-fibroblast interactions are critical for skin repair after injury. During the proliferative phase of wound healing, proliferation, migration and differentiation of these cells are the major mechanisms leading to tissue remodeling. We have previously reported that glycitin, a major soy isoflavone, stimulates dermal fibroblast proliferation; and the phytochemical, 4′,6,7-trimethoxyisoflavone (TMF), induces migration of HaCaT keratinocyte cells. We therefore investigated whether these compounds displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…Increasing numbers of studies are now focusing on the paracrine signalling and interaction between keratinocytes and fibroblasts in the context of wound repair [52,67]. To test our hypothesis that CAP-induced stimulatory effects in coculture are a result of paracrine crosstalk, we monitored the cell migration of HaCaTs that were incubated with conditioned media harvested from CAP-treated GM Fbs (GM-Fb-CM) collected after 18 hr of CAP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing numbers of studies are now focusing on the paracrine signalling and interaction between keratinocytes and fibroblasts in the context of wound repair [52,67]. To test our hypothesis that CAP-induced stimulatory effects in coculture are a result of paracrine crosstalk, we monitored the cell migration of HaCaTs that were incubated with conditioned media harvested from CAP-treated GM Fbs (GM-Fb-CM) collected after 18 hr of CAP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were cultured in RPMI medium 1640 containing 10% heat inactivated fetal bovine serum. Cells were exposed to a dose of 30 mJ/cm 2 of UVB (CL-1000 M UV Crosslinker, Upland, CA, USA) [ 32 ]. BDB was purchased from Matrix Scientific (Columbia, SC, USA) and the purity was above 95%.…”
Section: Methodsmentioning
confidence: 99%
“…ROS mainly function in a normal wound healing response, especially in dermal fibroblasts. Furthermore, NADPH oxidase (NOX) family is an important source of ROS generation [17]. For example, Sampson et al demonstrated the ROS signaling by NOX4, which induces fibroblast transformation of myofibroblast by increasing phosphorylation of JNK.…”
Section: Mechanisms Of Action Of the S Commune Beta-glucan On Epithementioning
confidence: 99%